VULGARISM: ITS CONCEPT AND CHARACTERISTICS Elamonova Gulsoatbonu Qahramon (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article explores the concept of vulgarism in linguistics, focusing on its social, cultural, and stylistic aspects. Vulgarisms are defined as words or expressions that violate moral or ethical norms and are often used to express strong emotions such as anger, irritation, or excitement. The study discusses the main characteristics of vulgar words, their evolution through time, and their functions in modern English. The paper also compares the role of vulgarisms in English and Uzbek languages, emphasizing their emotional power, social limitations, and cultural dependence. Understanding vulgarism helps to better comprehend how language reflects human behavior, cultural taboos, and social attitudes.